2020
DOI: 10.3389/fgene.2020.00484
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Evolutionary Analysis of NBS-LRR Genes From Dioscorea rotundata

Abstract: Dioscorea rotundata is an important food crop that is mainly cultivated in subtropical regions of the world. D. rotundata is frequently infected by various pathogens during its lifespan, which results in a substantial economic loss in terms of yield and quality. The disease resistance gene (R gene) profile of D. rotundata is largely unknown, which has greatly hampered molecular study of disease resistance in this species. Nucleotidebinding site-leucine-rich repeat (NBS-LRR) genes are the largest group of plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 49 publications
1
31
0
Order By: Relevance
“…Sequence alignment and phylogenetic analysis were performed as described by Shao et al (2014) ; Zhang Y. M. et al (2020) . Briefly, amino acid sequences of the conserved NBS domain encoded by barley NLR genes were retrieved and aligned using ClustalW with default options, and then manually corrected in MEGA 7.0 ( Kumar et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Sequence alignment and phylogenetic analysis were performed as described by Shao et al (2014) ; Zhang Y. M. et al (2020) . Briefly, amino acid sequences of the conserved NBS domain encoded by barley NLR genes were retrieved and aligned using ClustalW with default options, and then manually corrected in MEGA 7.0 ( Kumar et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…A typical NBS-encoding gene consists of a variable domain at the N-terminal, a highly conserved NBS domain in the middle, and a diverse leucine-rich repeat (LRR) domain at the C-terminal. Therefore, according to the structure of N-terminal domains that possess a coiled-coil (CC), Drosophila toll and mammalian interleukin-1 receptor-like (TIR), or resistance to powdery mildew8 (RPW8) domain, NBS-encoding genes can be classified into three subclasses: CC-NBS-LRR (CNL), TIR-NBS-LRR (TNL), and RPW8-NBS-LRR (RNL) ( Meyers et al, 2003 ; Shao et al, 2014 , 2016 , 2019 ; Zhang et al, 2016 , 2020 ; Qian et al, 2017 ; Xue et al, 2020 ). As an example of function, the CNL gene, RPP8 , in Arabidopsis thaliana provides resistance against downy mildew after Peronospora parasiticia infection ( Mcdowell et al, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the expression of the FtsZ2-1 gene under various stresses was researched. Tubulin genes were screened from the cassava genome, along with six other species, for instance, Arabidopsis thaliana [ 52 ], Dioscorea rotundata [ 53 ], Hevea brasiliensis [ 54 ], Oryza sativa [ 55 ], and Vitis vinifera [ 56 ]. In this study, 23 cassava tubulins were found and renamed as MeTubulin1 to MeTubulin23 in the order of screening, lower than Hevea brasiliensis (31), but higher than Arabidopsis thaliana (16), Dioscorea rotundata (11), Oryza sativa (16), and Vitis vinifera (18); according to amino acid sequences, motif composition, intron structure, phylogenetic feature, and tubulin type of cassava, the 23 cassava tubulin genes can be divided into four main groups.…”
Section: Discussionmentioning
confidence: 99%